2019
DOI: 10.1007/s12576-019-00707-3
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8-mediated cutaneous stimulation modulates motor neuron activity during treadmill stepping in mice

Abstract: Motor units are generally recruited from the smallest to the largest following the size principle, while cutaneous stimulation has the potential to affect spinal motor control. We aimed to examine the effects of stimulating transient receptor potential channel sub-family M8 (TRPM8) combined with exercise on the modulation of spinal motor neuron (MN) excitability. Mice were topically administrated 1.5% icilin on the hindlimbs, followed by treadmill stepping. Spinal cord sections were immunostained with antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Immunostaining of the spinal cord was performed as described previously [ 28 ]. Briefly, the vertebral column containing the spinal cord was dissected and post-fixed in 4% paraformaldehyde overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunostaining of the spinal cord was performed as described previously [ 28 ]. Briefly, the vertebral column containing the spinal cord was dissected and post-fixed in 4% paraformaldehyde overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Immunostaining of the spinal cord was performed as described previously [28]. Briefly, the vertebral column containing the spinal cord was dissected and post-fixed in 4% paraformaldehyde overnight at 4 • C. The lower lumbar segments (L3-L5) of the spinal cords were isolated and impregnated with 30% sucrose in PBS for over 3 days at 4 • C, followed by embedding in OCT compound (Sakura Finetek Japan, Osaka, Japan) and stored at −80 • C. The spinal cords were sectioned to a thickness of 30 µm using a cryostat (Leica, Wetzlar, Germany).…”
Section: Spinal Cord Histologymentioning
confidence: 99%
“…35% maximal voluntary contraction) may increase muscle strength 9) . Cutaneous stimulation with skin cooling has also been shown to modulate polysynaptic neural pathways, and a neural connection between skin cold receptors (transient receptor potential melastatin 8: TRPM8) and the motor neuron pool has been observed [10][11][12] . Skin cooling over the working muscle, without reducing the temperature of the muscle, facilitates preferential recruitment of large motor neurons 10) and reduces the recruitment threshold of fast muscle fibers 12) .…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous stimulation with skin cooling has also been shown to modulate polysynaptic neural pathways, and a neural connection between skin cold receptors (transient receptor potential melastatin 8: TRPM8) and the motor neuron pool has been observed [10][11][12] . Skin cooling over the working muscle, without reducing the temperature of the muscle, facilitates preferential recruitment of large motor neurons 10) and reduces the recruitment threshold of fast muscle fibers 12) . Several previous studies have also demonstrated a change in motor unit (MU) recruitment pattern, and MU recruitment thresholds were lower during voluntary contractions through spinal afferent input with electrical stimulation 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Higher exercise efficiency during certain intensity movements increases enjoyment during exercise and promotes motivation for further spontaneous exercise, which is needed to prevent the development of locomotive syndrome or sarcopenia. Exercise efficiency involves adaptations of the skeletal muscle metabolism, respiratory-cardiovascular system, hemodynamics and motor skills [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%